Design and Prototyping Single-Phase Inverter with Arduino Nano - Hari Maghfiroh; Augustinus Sujono; M. Iqbal Zidny; Taufik Widyastama (Universitas Sebelas Maret (UNS), 2021)
Across the year, the needs of Indonesians in the use of electronic equipment are increasing, which results in higher electricity usage. Because most of the electricity load uses AC power, in the application of a DC power source such as solar cells, an inverter that converts DC to AC power is needed. Therefore, the inverter is one of the tools that are widely developed in power electronics. The output voltage from simulation and real hardware is a sine wave with some distortion due to lack of filter; therefore, there occurs a harmonic. The voltage and frequency were also measured with a multimeter. The result shows that both voltage and frequency are closed to the design specification which is 220V 50Hz with the voltage and frequency difference of 1.09% and 0.4%, respectively.